2021
DOI: 10.3390/ijerph181910118
|View full text |Cite
|
Sign up to set email alerts
|

Exposure Profile to Traffic Related Pollution in Pediatric Age: A Biomonitoring Study

Abstract: The aim of this study was to trace an exposure profile to traffic-derived pollution during pediatric age. For this purpose, two biomonitoring campaigns for the determination of urinary (u-) methyl tert-butyl ether (MTBE), ethyl tert-butyl ether (ETBE), tert-amyl methyl ether (TAME), and diisopropyl ether (DIPE) were carried out in two different periods of the year (summer 2017 and winter 2018), among a large sample of healthy children (n = 736; 5–11 years old) living in rural and urban areas in central Italy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 36 publications
1
0
1
Order By: Relevance
“…In this sense, a significant result of this study is the relatively high participation rate, which benefited from the participatory approach of the study, as showed by the increased participation in the second campaign (Boniardi et al, 2021a). The overall BEN-U median level (44.9 ng/L) was similar to that reported for Italian children living in Central Italy in 2017 (winter mean 41.1 ng/L) (Antonucci et al, 2021), higher than in children living near or far from a petrochemical plant in Sardinia (Italy) in 2016 (10 ng/L) (Pilia et al, 2021), and much lower than in children living near or far from a petrochemical plant in Sicily in 2015 (Italy) (200 ng/L) (Andreoli et al, 2015), or in a urban area in Thailand in 2004 (70 ng/g creatinine) (Buthbumrung et al, 2008). BEN-U median levels were also slightly lower than in nonsmoking adults in Milan (67 ng/L) (Cattaneo et al, 2021).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In this sense, a significant result of this study is the relatively high participation rate, which benefited from the participatory approach of the study, as showed by the increased participation in the second campaign (Boniardi et al, 2021a). The overall BEN-U median level (44.9 ng/L) was similar to that reported for Italian children living in Central Italy in 2017 (winter mean 41.1 ng/L) (Antonucci et al, 2021), higher than in children living near or far from a petrochemical plant in Sardinia (Italy) in 2016 (10 ng/L) (Pilia et al, 2021), and much lower than in children living near or far from a petrochemical plant in Sicily in 2015 (Italy) (200 ng/L) (Andreoli et al, 2015), or in a urban area in Thailand in 2004 (70 ng/g creatinine) (Buthbumrung et al, 2008). BEN-U median levels were also slightly lower than in nonsmoking adults in Milan (67 ng/L) (Cattaneo et al, 2021).…”
Section: Discussionsupporting
confidence: 83%
“…BEN-U median levels were also slightly lower than in nonsmoking adults in Milan (67 ng/L) (Cattaneo et al, 2021). As regards MTBE-U, overall median levels (11.5 ng/L) were much lower than data previously reported for children in Italy (70-800 ng/L) (Andreoli et al, 2015;Antonucci et al, 2021) and in a selected population of Milan policemen exposed to traffic during work shifts (147 ng/L) (Campo et al, 2011). Both Pearson's correlation and mixed effect regression models showed that urinary biomarkers were significantly associated with their respective airborne levels, with r = 0.31 (BEN-U vs. BEN-A) and r = 0.57 (MTBE-U vs. MTBE-A) (Fig.…”
Section: Discussioncontrasting
confidence: 50%